A kind of water-based acrylic painting pigment and preparation method thereof
By introducing cellulose-acrylate copolymer and functionalized nanotitanium dioxide into aqueous acrylic painting pigments, the problems of pigments aging, cracking and fading in the sun are solved, and higher light resistance, color fastness and antibacterial properties are achieved.
Patent Information
- Application Number
- CN202411485811.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-23
AI Technical Summary
When existing acrylic painting pigments are exposed to sunlight for a long time, they are susceptible to excitation from ultraviolet rays and visible light, causing the pigments to age, crack and fade, and lack heat and light resistance.
The cellulose-acrylate copolymer emulsion was prepared by reacting hydroxyethyl cellulose, methyl acrylate, butyl acrylate and allyloxy triazine ultraviolet absorber, and the nanotitanium dioxide was reacted with silicone oligomer to produce functionalized nanotitanium dioxide. The pigment toner, dispersant, defoaming agent and water were uniformly mixed to prepare aqueous acrylic painting pigments.
It improves the protection effect of aqueous acrylic painting pigments on ultraviolet rays, extends the service life of the pigments, enhances its light resistance and color fastness, and improves the antibacterial and high-temperature resistance of the pigments.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of painting pigments, in particular to a water-based acrylic painting pigment and a preparation method thereof. Background Art
[0002] Acrylic paint is a synthetic polymer pigment. Since its birth in the 1950s, it has been widely used around the world. With the improvement of people's understanding of the characteristics of acrylic paint and the continuous maturity of the exploration of acrylic techniques, acrylic painting has gradually become an independent painting genre and has gradually revealed its unique charm. Compared with traditional pigments, acrylic paint is the latest pigment variety in the current pigment system but the most modern one. Acrylic paint has many characteristics that are superior to other pigments. It can flexibly change its own structure and is suitable for painting on various surfaces. In terms of expression techniques, acrylic paint shows great flexibility. It can achieve the transparency of watercolor paint, the thickness of oil paint, the covering power of gouache paint, and the elegance and softness of other emulsion pigments. Acrylic paint can achieve almost all of them. It can be used for painting independently and can also be compatible with other pigments.
[0003] However, when paintings are exposed to sunlight for a long time, the ultraviolet and visible light in the light have high energy. Under the action of these energies, they will stimulate the electron transition in the pigment molecules, thereby catalyzing the changes in the pigment molecules in the pigment and accelerating the aging, cracking and fading process of the pigment. Therefore, it is necessary to improve the heat and light resistance of acrylic paint. Summary of the invention
[0004] The purpose of the present invention is to provide a water-based acrylic painting pigment and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A water-based acrylic painting pigment, wherein the water-based acrylic painting pigment is prepared by reacting hydroxyethyl cellulose, methyl acrylate, butyl acrylate and allyloxytriazine ultraviolet absorber to obtain cellulose-acrylate copolymer emulsion; reacting nano titanium dioxide with siloxane oligomer and 1-chlorohexane in sequence to obtain functionalized nano titanium dioxide; and uniformly mixing the cellulose-acrylate copolymer emulsion, functionalized nano titanium dioxide, pigment powder, dispersant, defoamer and water to obtain the pigment;
[0007] The allyloxy triazine ultraviolet absorber is prepared by reacting 2-(allyloxy)-4,6-dichloro-1,3,5-triazine and resorcinol;
[0008] The siloxane oligomer is prepared by reacting tetramethylcyclotetrasiloxane and N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane).
[0009] A method for preparing a water-based acrylic paint, comprising the following steps:
[0010] (1) Add 2-(allyloxy)-4,6-dichloro-1,3,5-triazine and resorcinol in a molar ratio of 1:2 to chlorobenzene with a mass of 8 to 10 times that of 2-(allyloxy)-4,6-dichloro-1,3,5-triazine, add anhydrous aluminum chloride with a mass of 0.03 to 0.05 times that of 2-(allyloxy)-4,6-dichloro-1,3,5-triazine, stir at 10 to 30° C. and 300 to 500 r / min for 20 to 30 minutes, heat to 90 to 96° C., continue stirring for 5 to 6 hours, add hydrochloric acid aqueous solution with a volume of 1 to 2 times that of chlorobenzene, mix evenly, filter, wash with deionized water for 3 to 5 times, and dry at 50 to 60° C. under vacuum conditions for 8 to 10 hours to obtain an allyloxy triazine ultraviolet absorber;
[0011] (2) 0.2-0.3 times the mass of the mixed monomer and deionized water are mixed uniformly in a mass ratio of 1:(4-6), stirred at 70-80°C and 300-500 r / min for 10-20 min, and sodium bicarbonate 0.03-0.05 times the mass of the hydroxyethyl cellulose is added under a nitrogen atmosphere, and an initiator solution accounting for half the mass of the initiator solution is added, and stirring is continued for 8-10 min. Within 5 min, a mixed monomer accounting for one quarter of the mass of the mixed monomer is added dropwise at a uniform rate, and the stirring reaction is continued for 20-30 min. Within 10 min, the remaining mixed monomer and the remaining initiator solution are added dropwise at a uniform rate at the same time, and stirring is continued for 4-5 h. After cooling to room temperature, the material is discharged to obtain a cellulose-acrylate copolymer emulsion;
[0012] (3) Mix nano-titanium dioxide and anhydrous ethanol at a mass ratio of 1:(80-100) and disperse them evenly, perform ultrasonic dispersion for 50-60 min, add 1.2-1.4 times the mass of nano-titanium dioxide siloxane oligomer, add 0.07-0.09 times the mass of nano-titanium dioxide dibutyltin dilaurate, stir at 25-35°C and 300-500 r / min for 2-3 h under nitrogen protection, filter, and place under vacuum. , drying at 50-60°C for 16-18h to obtain modified nano titanium dioxide; uniformly mixing the modified nano titanium dioxide, 1-chlorohexane and anhydrous acetone in a mass ratio of 1:(2-3):(12-14), stirring at 50-60°C and 300-500r / min for 4-5h, filtering, washing with anhydrous acetone for 3-5 times, and drying at 50-60°C under vacuum conditions for 8-10h to obtain functionalized nano titanium dioxide;
[0013] (4) Weigh 36-42 parts of cellulose-acrylate copolymer emulsion, 8-10 parts of functionalized nano titanium dioxide, 10-12 parts of pigment toner, 0.2-1.5 parts of FX365 dispersant, 0.2-2.5 parts of SPA-202 defoamer, and 9-13 parts of water, and mix them evenly. Stir at room temperature at 300-500 r / min for 8-10 minutes to prepare a water-based acrylic painting pigment.
[0014] As an optimization, the mass fraction of the hydrochloric acid aqueous solution in step (1) is 10% to 12%.
[0015] As an optimization, the preparation method of the mixed monomer in step (2) is: methyl acrylate, butyl acrylate, and allyloxytriazine ultraviolet absorber are mixed in a molar ratio of 1:1:(0.4-0.6) to prepare a mixed monomer.
[0016] As an optimization, the molecular weight of the hydroxyethyl cellulose in step (2) is 10,000 to 20,000.
[0017] As an optimization, the preparation method of the initiator solution in step (2) is: 0.01 to 0.02 times the mass of the mixed monomers and potassium persulfate and deionized water are mixed in a mass ratio of 1: (8 to 10) to prepare an initiator solution.
[0018] As an optimization, the preparation method of the siloxane oligomer in step (3) is: tetramethylcyclotetrasiloxane, N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane), tetramethylammonium hydroxide, dimethyl sulfoxide and toluene are mixed uniformly, stirred at 65-75°C and 300-500r / min for 20-30min, cooled to room temperature, washed with an equal volume of deionized water and toluene, allowed to stand for stratification, the aqueous phase is removed, the washing is repeated 3-5 times, the organic phase is placed in a drying oven, and dried at 50-60°C under vacuum conditions for 8-10h to obtain the siloxane oligomer.
[0019] As an optimization, the mass ratio of the tetramethylcyclotetrasiloxane, N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxyl)]tri(N-ethyl-ethane), tetramethylammonium hydroxide, dimethyl sulfoxide, and toluene is 1:(0.6-0.8):(0.01-0.03):(0.01-0.03):(10-12).
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] When preparing water-based acrylic painting pigment, the present invention comprises the following steps: reacting 2-(allyloxy)-4,6-dichloro-1,3,5-triazine and resorcinol to obtain an allyloxy triazine ultraviolet absorber; reacting hydroxyethyl cellulose, methyl acrylate, butyl acrylate and an allyloxy triazine ultraviolet absorber to obtain a cellulose-acrylate copolymer emulsion; reacting tetramethylcyclotetrasiloxane and N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane) to obtain a siloxane oligomer; reacting nano titanium dioxide and a siloxane oligomer to obtain modified nano titanium dioxide; reacting the modified nano titanium dioxide and 1-chlorohexane to obtain functionalized nano titanium dioxide; and uniformly mixing the cellulose-acrylate copolymer emulsion, the functionalized nano titanium dioxide, a pigment toner, a dispersant, a defoamer and water to obtain a water-based acrylic painting pigment.
[0022] First, 2-(allyloxy)-4,6-dichloro-1,3,5-triazine and resorcinol are reacted to obtain an allyloxytriazine ultraviolet absorber, and hydroxyethyl cellulose, methyl acrylate, butyl acrylate, and allyloxytriazine ultraviolet absorbers are reacted to obtain a cellulose-acrylate copolymer emulsion; part of the hydroxyl groups on the hydroxyethyl cellulose generate active oxygen free radicals under the action of an initiator, potassium persulfate, and copolymerize with the carbon-carbon double bonds on methyl acrylate, butyl acrylate, and allyloxytriazine ultraviolet absorbers, so that methyl acrylate, butyl acrylate, and allyloxytriazine ultraviolet absorbers are grafted onto the hydroxyethyl cellulose to obtain a cellulose-acrylate copolymer emulsion, and a hydrogen bond hexacyclic ring is introduced into the cellulose-acrylate copolymer emulsion to absorb ultraviolet light, thereby improving the protective effect of water-based acrylic painting pigments against ultraviolet rays contained in sunlight, reducing the influence of ultraviolet rays in light on pigments, and thereby improving the color fastness of the water-based acrylic painting pigments, improving the light resistance of the water-based acrylic painting pigments, and extending the service life of the water-based acrylic painting pigments.
[0023] Secondly, tetramethylcyclotetrasiloxane and N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane) are reacted to obtain siloxane oligomers, and Si-H bonds and tertiary amine structures are introduced into the molecular chains of the siloxane oligomers; nano-titanium dioxide and siloxane oligomers are reacted to obtain modified nano-titanium dioxide; the hydroxyl groups on the nano-titanium dioxide react with the Si-H bonds on the siloxane oligomers, The siloxane oligomer is grafted on the surface of nano-silicon dioxide; the modified nano-titanium dioxide and 1-chlorohexane are reacted to obtain functionalized nano-titanium dioxide; the tertiary amine structure on the siloxane oligomer grafted on the surface of the modified nano-titanium dioxide reacts with the chlorine on the 1-chlorohexane to generate a quaternary ammonium salt structure, which has antibacterial properties and can prevent water-based acrylic painting pigments from becoming moldy and deteriorating; at the same time, the siloxane oligomer contains a large amount of Si-O, which can improve the high temperature resistance of the water-based acrylic painting pigment. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] Embodiment 1:
[0026] A method for preparing a water-based acrylic paint, comprising the following steps:
[0027] (1) adding 2-(allyloxy)-4,6-dichloro-1,3,5-triazine and resorcinol in a molar ratio of 1:2 to chlorobenzene with a mass of 8 times that of 2-(allyloxy)-4,6-dichloro-1,3,5-triazine, adding anhydrous aluminum chloride with a mass of 0.03 times that of 2-(allyloxy)-4,6-dichloro-1,3,5-triazine, stirring at 10° C. and 300 r / min for 30 minutes, heating to 90° C. and continuing stirring for 6 hours, adding a 10% hydrochloric acid aqueous solution with a mass fraction of 1 times that of chlorobenzene, mixing evenly, filtering, washing with deionized water 3 times, and drying at 50° C. for 10 hours under vacuum conditions to obtain an allyloxy triazine ultraviolet absorber;
[0028] (2) Methyl acrylate, butyl acrylate, and allyloxytriazine ultraviolet absorber are mixed in a molar ratio of 1:1:0.4 to prepare a mixed monomer; potassium persulfate (0.01 times the mass of the mixed monomer) and deionized water (1:8) are mixed evenly to prepare an initiator solution; hydroxyethyl cellulose (0.2 times the mass of the mixed monomer) and deionized water (1:4) are mixed evenly, stirred at 70°C and 300 r / min for 20 minutes, sodium bicarbonate (0.03 times the mass of the hydroxyethyl cellulose) is added under a nitrogen atmosphere, an initiator solution (half the mass of the initiator solution) is added, stirring is continued for 10 minutes, a mixed monomer (one quarter the mass of the mixed monomer) is added dropwise at a uniform rate within 5 minutes, stirring is continued for 30 minutes, the remaining mixed monomer and the remaining initiator solution are added dropwise at a uniform rate within 10 minutes, stirring is continued for 5 hours, cooling to room temperature and then discharging to obtain a cellulose-acrylate copolymer emulsion;
[0029] (3) Tetramethylcyclotetrasiloxane, N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane), tetramethylammonium hydroxide, dimethyl sulfoxide and toluene were mixed uniformly in a mass ratio of 1:0.6:0.01:0.01:10, stirred at 65°C and 300 r / min for 30 min, cooled to room temperature, washed with an equal volume of deionized water and toluene, allowed to stand for stratification, the aqueous phase was removed, and the washing was repeated 3 times. The organic phase was placed in a drying oven and dried at 50°C for 10 h under vacuum conditions to obtain a siloxane oligomer; nano-titanium dioxide and anhydrous ethyl acetate were added. The alcohol was mixed evenly at a mass ratio of 1:80, ultrasonically dispersed for 50 minutes, 1.2 times the mass of nano-titanium dioxide was added with siloxane oligomer, 0.07 times the mass of nano-titanium dioxide was added with dibutyltin dilaurate, and stirred for 3 hours at 25°C and 300r / min under nitrogen protection, filtered, and dried at 50°C for 18 hours under vacuum conditions to obtain modified nano-titanium dioxide; the modified nano-titanium dioxide, 1-chlorohexane, and anhydrous acetone were mixed evenly at a mass ratio of 1:2:12, stirred for 5 hours at 50°C and 300r / min, filtered, washed with anhydrous acetone 3 times, and dried at 50°C for 10 hours under vacuum conditions to obtain functionalized nano-titanium dioxide;
[0030] (4) 36 parts by mass of cellulose-acrylate copolymer emulsion, 8 parts by mass of functionalized nano titanium dioxide, 10 parts by mass of Golden Red C, 0.2 parts by mass of FX365 dispersant, 0.2 parts by mass of SPA-202 defoamer, and 9 parts by mass of water were mixed and stirred at 300 r / min for 10 min at room temperature to prepare a water-based acrylic painting pigment.
[0031] Embodiment 2:
[0032] A method for preparing a water-based acrylic paint, comprising the following steps:
[0033] (1) adding 2-(allyloxy)-4,6-dichloro-1,3,5-triazine and resorcinol in a molar ratio of 1:2 to chlorobenzene with a mass of 9 times that of 2-(allyloxy)-4,6-dichloro-1,3,5-triazine, adding anhydrous aluminum chloride with a mass of 0.04 times that of 2-(allyloxy)-4,6-dichloro-1,3,5-triazine, stirring at 20° C. and 400 r / min for 25 min, heating to 93° C., stirring for 5.5 h, adding 11% hydrochloric acid aqueous solution with a mass fraction of 1.5 times that of chlorobenzene, mixing evenly, filtering, washing with deionized water 4 times, and drying at 55° C. under vacuum conditions for 9 h to obtain an allyloxy triazine ultraviolet absorber;
[0034] (2) Methyl acrylate, butyl acrylate, and allyloxytriazine ultraviolet absorber are mixed in a molar ratio of 1:1:0.5 to prepare a mixed monomer; potassium persulfate (0.015 times the mass of the mixed monomer) and deionized water (1:9) are mixed evenly to prepare an initiator solution; hydroxyethyl cellulose (0.25 times the mass of the mixed monomer) and deionized water (1:5) are mixed evenly, stirred at 75°C and 400 r / min for 15 minutes, sodium bicarbonate (0.04 times the mass of the hydroxyethyl cellulose) is added under a nitrogen atmosphere, an initiator solution (half the mass of the initiator solution) is added, stirring is continued for 9 minutes, a mixed monomer (one quarter the mass of the mixed monomer) is added dropwise at a uniform speed within 5 minutes, stirring is continued for 25 minutes, the remaining mixed monomer and the remaining initiator solution are added dropwise at a uniform speed within 10 minutes, stirring is continued for 4.5 hours, cooling to room temperature and then discharging to obtain a cellulose-acrylate copolymer emulsion;
[0035] (3) Tetramethylcyclotetrasiloxane, N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane), tetramethylammonium hydroxide, dimethyl sulfoxide, and toluene were uniformly mixed in a mass ratio of 1:0.7:0.02:0.02:11, stirred at 70°C and 400 r / min for 25 min, cooled to room temperature, washed with an equal volume of deionized water and toluene, allowed to stand for stratification, the aqueous phase was removed, and the washing was repeated 4 times. The organic phase was placed in a drying oven and dried at 55°C for 9 h under vacuum conditions to obtain a siloxane oligomer; nano-titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:0.7:0.02:0.02:11. The mixture was mixed evenly at a mass ratio of 1:90, ultrasonically dispersed for 55 minutes, 1.3 times the mass of nano-titanium dioxide was added with siloxane oligomer, 0.08 times the mass of nano-titanium dioxide was added with dibutyltin dilaurate, and stirred for 2.5 hours at 30°C and 400r / min under nitrogen protection, filtered, and dried at 55°C for 17 hours under vacuum conditions to obtain modified nano-titanium dioxide; the modified nano-titanium dioxide, 1-chlorohexane, and anhydrous acetone were mixed evenly at a mass ratio of 1:2.5:13, stirred for 4.5 hours at 55°C and 400r / min, filtered, washed with anhydrous acetone 4 times, and dried at 55°C for 9 hours under vacuum conditions to obtain functionalized nano-titanium dioxide;
[0036] (4) 39 parts of cellulose-acrylate copolymer emulsion, 9 parts of functionalized nano titanium dioxide, 11 parts of Jinguanghong C, 0.85 parts of FX365 dispersant, 1.35 parts of SPA-202 defoamer, and 11 parts of water were weighed and mixed evenly, and stirred at 400 r / min at room temperature for 9 minutes to prepare a water-based acrylic painting pigment.
[0037] Embodiment 3:
[0038] A method for preparing a water-based acrylic paint, comprising the following steps:
[0039] (1) adding 2-(allyloxy)-4,6-dichloro-1,3,5-triazine and resorcinol in a molar ratio of 1:2 to chlorobenzene with a mass of 10 times that of 2-(allyloxy)-4,6-dichloro-1,3,5-triazine, adding anhydrous aluminum chloride with a mass of 0.05 times that of 2-(allyloxy)-4,6-dichloro-1,3,5-triazine, stirring at 30° C. and 500 r / min for 20 min, heating to 96° C., stirring for 5 h, adding a 12% hydrochloric acid aqueous solution with a mass fraction of 2 times that of chlorobenzene, mixing evenly, filtering, washing with deionized water 5 times, and drying at 60° C. under vacuum conditions for 8 h to obtain an allyloxy triazine ultraviolet absorber;
[0040] (2) Methyl acrylate, butyl acrylate, and allyloxytriazine ultraviolet absorber are mixed in a molar ratio of 1:1:0.6 to prepare a mixed monomer; potassium persulfate (0.02 times the mass of the mixed monomer) and deionized water (1:10) are mixed evenly to prepare an initiator solution; hydroxyethyl cellulose (0.3 times the mass of the mixed monomer) and deionized water (1:6) are mixed evenly, stirred at 80°C and 500 r / min for 10 minutes, sodium bicarbonate (0.05 times the mass of the hydroxyethyl cellulose) is added under a nitrogen atmosphere, an initiator solution (half the mass of the initiator solution) is added, stirring is continued for 8 minutes, a mixed monomer (one quarter the mass of the mixed monomer) is added dropwise at a uniform rate within 5 minutes, stirring is continued for 20 minutes, the remaining mixed monomer and the remaining initiator solution are added dropwise at a uniform rate within 10 minutes, stirring is continued for 4 hours, cooling to room temperature and then discharging to obtain a cellulose-acrylate copolymer emulsion;
[0041] (3) Tetramethylcyclotetrasiloxane, N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane), tetramethylammonium hydroxide, dimethyl sulfoxide and toluene were mixed uniformly in a mass ratio of 1:0.8:0.03:0.03:12, stirred at 75°C and 500 r / min for 20 min, cooled to room temperature, washed with an equal volume of deionized water and toluene, allowed to stand for stratification, the aqueous phase was removed, and the washing was repeated 5 times. The organic phase was placed in a drying oven and dried at 60°C for 8 h under vacuum conditions to obtain a siloxane oligomer; nano-titanium dioxide and anhydrous ethyl acetate were added to the mixture. The alcohol was mixed evenly at a mass ratio of 1:100, ultrasonically dispersed for 60 minutes, 1.4 times the mass of nano-titanium dioxide was added with siloxane oligomer, 0.09 times the mass of nano-titanium dioxide was added with dibutyltin dilaurate, and stirred for 2 hours at 35°C and 500r / min under nitrogen protection, filtered, and dried at 60°C for 16 hours under vacuum conditions to obtain modified nano-titanium dioxide; the modified nano-titanium dioxide, 1-chlorohexane, and anhydrous acetone were mixed evenly at a mass ratio of 1:3:14, stirred for 4 hours at 60°C and 500r / min, filtered, washed with anhydrous acetone for 5 times, and dried at 60°C for 8 hours under vacuum conditions to obtain functionalized nano-titanium dioxide;
[0042] (4) Weigh 42 parts by mass of cellulose-acrylate copolymer emulsion, 10 parts by mass of functionalized nano titanium dioxide, 12 parts by mass of Golden Red C, 1.5 parts by mass of FX365 dispersant, 2.5 parts by mass of SPA-202 defoamer, and 13 parts by mass of water, mix them evenly, and stir at 500 r / min for 8 min at room temperature to prepare a water-based acrylic painting pigment.
[0043] Comparative Example 1:
[0044] The preparation method of the water-based acrylic painting pigment of Comparative Example 1 is different from that of Example 2 in that step (1) is not performed, and step (2) is modified as follows: methyl acrylate and butyl acrylate are mixed in a molar ratio of 1:1 to prepare a mixed monomer; potassium persulfate (0.015 times the mass of the mixed monomer) and deionized water (1:9) are mixed uniformly to prepare an initiator solution; hydroxyethyl cellulose (0.25 times the mass of the mixed monomer) and deionized water (1:5) are mixed uniformly, stirred at 75° C. and 400 r / min for 15 min, sodium bicarbonate (0.04 times the mass of the hydroxyethyl cellulose) is added under a nitrogen atmosphere, an initiator solution (half the mass of the initiator solution) is added, stirring is continued for 9 min, a mixed monomer (one quarter the mass of the mixed monomer) is added dropwise at a uniform speed within 5 min, stirring is continued for 25 min, the remaining mixed monomer and the remaining initiator solution are added dropwise at a uniform speed within 10 min, stirring is continued for 4.5 h, and the material is discharged after cooling to room temperature to obtain a cellulose-acrylate copolymer emulsion. The remaining steps are the same as in Example 2.
[0045] Comparative Example 2:
[0046] The preparation method of the water-based acrylic painting pigment of Comparative Example 2 is different from that of Example 2 in that step (3) is different. Step (3) is modified as follows: tetramethylcyclotetrasiloxane, N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane), tetramethylammonium hydroxide, dimethyl sulfoxide, and toluene are uniformly mixed in a mass ratio of 1:0.7:0.02:0.02:11, stirred at 70°C and 400r / min for 25min, cooled to room temperature, and washed with an equal volume of deionized water and toluene. The mixture was allowed to stand for stratification, the aqueous phase was removed, and the washing was repeated 4 times. The organic phase was placed in a drying oven and dried at 55°C for 9 hours under vacuum conditions to obtain a siloxane oligomer. Nano-titanium dioxide and anhydrous ethanol were mixed evenly at a mass ratio of 1:90, ultrasonically dispersed for 55 minutes, 1.3 times the mass of nano-titanium dioxide was added to the siloxane oligomer, 0.08 times the mass of nano-titanium dioxide was added to the dibutyltin dilaurate, and the mixture was stirred at 30°C and 400r / min for 2.5 hours under nitrogen protection, filtered, and dried at 55°C for 17 hours under vacuum conditions to obtain functionalized nano-titanium dioxide. The remaining steps were the same as those in Example 2.
[0047] Comparative Example 3:
[0048] The preparation method of the water-based acrylic paint in Comparative Example 3 is different from that in Example 2 in that step (3) is not performed, and step (4) is modified as follows: 39 parts of cellulose-acrylate copolymer emulsion, 9 parts of nano titanium dioxide, 11 parts of Jinguanghong C, 0.85 parts of FX365 dispersant, 1.35 parts of SPA-202 defoamer, and 11 parts of water are weighed by mass, mixed evenly, and stirred at 400 r / min for 9 minutes at room temperature to obtain a water-based acrylic paint. The remaining steps are the same as in Example 2.
[0049] Test Example 1
[0050] Anti-mildew performance test
[0051] Test method: The mildew resistance of the examples and comparative examples was tested according to QB / T4289-2012. The results are shown in Table 1.
[0052] Table 1
[0053] Is mildew occurring? Is mildew occurring? Example 1 no Comparative Example 1 no Example 2 no Comparative Example 2 yes Example 3 no Comparative Example 3 yes
[0054] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the water-based acrylic painting pigment prepared by the present invention has good anti-mildew performance.
[0055] By comparison, none of Examples 1 to 3 mildewed, while Comparative Examples 2 to 3 mildewed, indicating that tetramethylcyclotetrasiloxane and N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane) were reacted to prepare siloxane oligomers, and Si-H bonds and tertiary amine structures were introduced into the siloxane oligomer molecular chains; nano-titanium dioxide and siloxane oligomers were reacted to prepare modified The invention discloses a method for preparing functional nano titanium dioxide; the hydroxyl group on the nano titanium dioxide reacts with the Si-H bond on the siloxane oligomer to graft the siloxane oligomer on the surface of the nano silicon dioxide; the modified nano titanium dioxide and 1-chlorohexane are reacted to obtain functional nano titanium dioxide; the tertiary amine structure on the siloxane oligomer grafted on the surface of the modified nano titanium dioxide reacts with the chlorine on the 1-chlorohexane to form a quaternary ammonium salt structure, which has antibacterial properties and can prevent water-based acrylic painting pigments from becoming moldy and deteriorating.
[0056] Test Example 2
[0057] Lightfastness test
[0058] Test method: The light resistance levels of the examples and comparative examples were tested according to QB / T4289-2012. The results are shown in Table 2
[0059] Table 2
[0060] Light resistance level Light resistance level Example 1 Level 7 Comparative Example 1 Level 4 Example 2 Level 7 Comparative Example 2 Level 7 Example 3 Level 7 Comparative Example 3 Level 7
[0061] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the water-based acrylic painting pigment prepared by the present invention has good light resistance.
[0062] By comparison, the light resistance levels of Examples 1 to 3 are greater than that of Comparative Example 1, indicating that 2-(allyloxy)-4,6-dichloro-1,3,5-triazine and resorcinol are reacted to obtain an allyloxy triazine UV absorber, and hydroxyethyl cellulose, methyl acrylate, butyl acrylate, and allyloxy triazine UV absorber are reacted to obtain a cellulose-acrylate copolymer emulsion; some hydroxyl groups on the hydroxyethyl cellulose generate active oxygen free radicals under the action of the initiator potassium persulfate, and react with methyl acrylate, butyl acrylate, and allyloxy triazine UV absorber to obtain an active oxygen free radical. The carbon-carbon double bonds on the agent are copolymerized, so that methyl acrylate, butyl acrylate, and allyloxytriazine UV absorbers are grafted onto hydroxyethyl cellulose to prepare cellulose-acrylate copolymer emulsion, and hydrogen bond six-membered rings are introduced into the cellulose-acrylate copolymer emulsion to absorb ultraviolet light, thereby improving the protection effect of water-based acrylic painting pigments against ultraviolet rays contained in sunlight, reducing the influence of ultraviolet rays in light on pigments, thereby improving the color fastness of water-based acrylic painting pigments, improving the light resistance of water-based acrylic painting pigments, and extending the service life of water-based acrylic painting pigments.
[0063] Test Example 3
[0064] High temperature resistance test
[0065] Test method: According to the GB / T1735-2009 test specification, the embodiments and comparative examples are prepared into standard samples, and the high temperature resistance of the standard samples is tested. The program heating steps are set, and the heating rate is set to 2°C / min. When it reaches 300°C, it is kept warm for 2 hours, and then the power is turned off for natural cooling. After cooling to room temperature, the sample is taken out and the surface state of the standard sample is observed with a magnifying glass. If the standard sample does not crack or bulge, it means that the high temperature resistance is excellent. The results are shown in Table 3.
[0066] Table 3
[0067] Cracking Cracking Example 1 No cracks Comparative Example 1 No cracks Example 2 No cracks Comparative Example 2 No cracks Example 3 No cracks Comparative Example 3 Slight cracks
[0068] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the water-based acrylic painting pigment prepared by the present invention has good high temperature resistance.
[0069] By comparison, none of Examples 1 to 3 had cracks, while Comparative Example 3 had cracks, indicating that tetramethylcyclotetrasiloxane and N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxyl)]tri(N-ethyl-ethane) were reacted to obtain siloxane oligomers, and Si-H bonds were introduced into the molecular chains of the siloxane oligomers; nano-titanium dioxide and siloxane oligomers were reacted to obtain modified nano-titanium dioxide; the hydroxyl groups on the nano-titanium dioxide reacted with the Si-H bonds on the siloxane oligomers to graft the siloxane oligomers onto the surface of the nano-silicon dioxide, and the large amount of Si-O on the siloxane oligomers could improve the high and low resistance of the water-based acrylic painting pigments.
[0070] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A water-based acrylic painting pigment, characterized in that: The water-based acrylic painting pigment is prepared by reacting hydroxyethyl cellulose, methyl acrylate, butyl acrylate and allyloxy triazine ultraviolet absorber to obtain cellulose-acrylate copolymer emulsion; reacting nano titanium dioxide with siloxane oligomer and 1-chlorohexane in sequence to obtain functionalized nano titanium dioxide; and uniformly mixing the cellulose-acrylate copolymer emulsion, functionalized nano titanium dioxide, pigment powder, dispersant, defoamer and water. The allyloxy triazine ultraviolet absorber is prepared by reacting 2-(allyloxy)-4,6-dichloro-1,3,5-triazine and resorcinol; The siloxane oligomer is prepared by reacting tetramethylcyclotetrasiloxane and N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane).
2. A method for preparing a water-based acrylic painting pigment, characterized in that: The preparation method of the water-based acrylic painting pigment comprises the following preparation steps: (1) Add 2-(allyloxy)-4,6-dichloro-1,3,5-triazine and resorcinol in a molar ratio of 1:2 to chlorobenzene with a mass of 8 to 10 times that of 2-(allyloxy)-4,6-dichloro-1,3,5-triazine, add anhydrous aluminum chloride with a mass of 0.03 to 0.05 times that of 2-(allyloxy)-4,6-dichloro-1,3,5-triazine, stir at 10 to 30° C. and 300 to 500 r / min for 20 to 30 minutes, heat to 90 to 96° C., continue stirring for 5 to 6 hours, add hydrochloric acid aqueous solution with a volume of 1 to 2 times that of chlorobenzene, mix evenly, filter, wash with deionized water for 3 to 5 times, and dry at 50 to 60° C. under vacuum conditions for 8 to 10 hours to obtain an allyloxy triazine ultraviolet absorber; (2) Methyl acrylate, butyl acrylate and allyloxytriazine ultraviolet absorber are mixed in a molar ratio of 1:1:(0.4-0.6) to prepare a mixed monomer; 0.2-0.3 times the mass of the mixed monomer and deionized water are mixed in a mass ratio of 1:(4-6) and stirred at 70-80°C and 300-500r / min for 10-20min; sodium bicarbonate in an amount of 0.03-0.05 times the mass of the hydroxyethyl cellulose is added under a nitrogen atmosphere; an initiator solution accounting for half the mass of the initiator solution is added; stirring is continued for 8-10min; a mixed monomer accounting for one quarter of the mass of the mixed monomer is added dropwise at a uniform speed within 5min; stirring is continued for 20-30min; the remaining mixed monomer and the remaining initiator solution are added dropwise at a uniform speed within 10min; stirring is continued for 4-5h; the material is discharged after cooling to room temperature to obtain a cellulose-acrylate copolymer emulsion; (3) Mix nano-titanium dioxide and anhydrous ethanol at a mass ratio of 1:(80-100) and disperse them evenly, perform ultrasonic dispersion for 50-60 min, add 1.2-1.4 times the mass of nano-titanium dioxide siloxane oligomer, add 0.07-0.09 times the mass of nano-titanium dioxide dibutyltin dilaurate, stir at 25-35°C and 300-500 r / min for 2-3 h under nitrogen protection, filter, and place under vacuum. , drying at 50-60°C for 16-18h to obtain modified nano titanium dioxide; uniformly mixing the modified nano titanium dioxide, 1-chlorohexane and anhydrous acetone in a mass ratio of 1:(2-3):(12-14), stirring at 50-60°C and 300-500r / min for 4-5h, filtering, washing with anhydrous acetone for 3-5 times, and drying at 50-60°C under vacuum conditions for 8-10h to obtain functionalized nano titanium dioxide; (4) Weigh 36-42 parts of cellulose-acrylate copolymer emulsion, 8-10 parts of functionalized nano titanium dioxide, 10-12 parts of pigment toner, 0.2-1.5 parts of FX365 dispersant, 0.2-2.5 parts of SPA-202 defoamer, and 9-13 parts of water, and mix them evenly. Stir at room temperature at 300-500 r / min for 8-10 minutes to prepare a water-based acrylic painting pigment.
3. The method for preparing a water-based acrylic paint according to claim 2, characterized in that: The mass fraction of the hydrochloric acid aqueous solution in step (1) is 10% to 12%.
4. The method for preparing a water-based acrylic painting pigment according to claim 2, characterized in that: The molecular weight of the hydroxyethyl cellulose in step (2) is 10,000 to 20,000.
5. The method for preparing a water-based acrylic painting pigment according to claim 2, characterized in that: The preparation method of the initiator solution in step (2) is as follows: potassium persulfate (0.01 to 0.02 times the mass of the mixed monomer) and deionized water are uniformly mixed in a mass ratio of 1:(8 to 10) to prepare an initiator solution.
6. The method for preparing a water-based acrylic painting pigment according to claim 2, characterized in that: The preparation method of the siloxane oligomer in step (3) is as follows: tetramethylcyclotetrasiloxane, N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane), tetramethylammonium hydroxide, dimethyl sulfoxide and toluene are uniformly mixed, stirred at 65-75°C and 300-500 r / min for 20-30 min, cooled to room temperature, washed with an equal volume of deionized water and toluene, allowed to stand for stratification, the aqueous phase is removed, the washing is repeated 3-5 times, the organic phase is placed in a drying oven, and dried at 50-60°C under vacuum conditions for 8-10 h to obtain the siloxane oligomer.
7. The method for preparing a water-based acrylic painting pigment according to claim 6, characterized in that: The mass ratio of the tetramethylcyclotetrasiloxane, N,N',N"-[(2,4,6,8,8-pentamethylcyclotetrasiloxane-2,4,6-triyl)tri(oxy)]tri(N-ethyl-ethane), tetramethylammonium hydroxide, dimethyl sulfoxide and toluene is 1:(0.6-0.8):(0.01-0.03):(0.01-0.03):(10-12).
Citation Information
Patent Citations
Cellulose graft copolymer ceramic slurry dispersing agent and preparation method thereof
CN102716694A
Ultraviolet curing waterborne coating and preparation method thereof
CN109135549A